Adaptability and change readiness among Malaysian public sector employees - Tan, Fee Cheng (2020)
Adaptability is of great importance to employees to remain competitive in a dynamic and uncertain work environment. It is, therefore, essential to understand the factors that may influence employees’ adaptability. Although much has been done to investigate positive change responses, i.e. change readiness, little is known about the relationship between adaptability and change readiness. Hence, this research aimed to study factors, namely managerial climate, on-the-job embeddedness, psychological ownership, and proactive personality that influence employees’ adaptability and its effect on change readiness in the context of Malaysian public sector organizations by drawing upon the Bandura’s (1986) social cognitive theory. The study was conducted during a historical change in the Malaysian government administration since independence. A quantitative approach was employed whereby questionnaires were administered to public sector organizations in Putrajaya and Kuala Lumpur. of 500 administrative and diplomatic officers approached using a systematic sampling technique, 386 responded to the survey. The data was analysed using SPSS and PLS-SEM. The results provide interesting insight into the factors influencing adaptability and change readiness. Managerial climate, psychological ownership, and on-the-job embeddedness were found to influence employees’ adaptability. While managerial climate and adaptability were found to influence change readiness, no significant influence of psychological ownership and on-the-job embeddedness on change readiness was observed. Meanwhile, adaptability was found to mediate the relationship between managerial climate, psychological ownership, on-the-job embeddedness, and change readiness. Besides that, proactive personality was shown to negatively moderate the relationship between adaptability and change readiness. This study enriched the adaptability literature by expanding knowledge of the relationship between the antecedents, employees’ adaptability, and change readiness. Managers are advised to create the right climate that helps employees better adapt and be ready to change over time. Subsequently, this will ensure change success in Malaysian public sector organizations.